2010
DOI: 10.2113/gsjfr.40.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Modern Calcification Depth of Globigerina Bulloides in the Southwestern Indian Ocean From Its Oxygen Isotopic Composition

Abstract: The water depth at which the planktic foraminiferal species Globigerina bulloides calcifies its shell has been deciphered based on the oxygen isotopic composition of its shells in surface sediment samples collected from the southwestern Indian Ocean. The seawater temperature for water depths ranging from 0−200 m was estimated from G. bulloides δ 18 O by using various paleotemperature equations. Out of several paleotemperature equations, the one given by Epstein and others (1953) provided the best-fit results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Planktic foraminifera G. bulloides inhabits the water above the thermocline at around 75 to 100 m 51 52 . The thermocline in the Indian sector of Southern Ocean is known to vary within the range of 75−150 m 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Planktic foraminifera G. bulloides inhabits the water above the thermocline at around 75 to 100 m 51 52 . The thermocline in the Indian sector of Southern Ocean is known to vary within the range of 75−150 m 53 .…”
Section: Resultsmentioning
confidence: 99%
“…4 is ±3 °C). Recent core-top sediments studies carried out in the Southwest Pacific Ocean (33–54°S) have shown that temperature reconstructions obtained with Mg/Ca on G. bulloides correlates best with water temperatures at 200 m depth 80 .…”
Section: Methodsmentioning
confidence: 99%
“…Hemleben et al (1989) suggest a depth above 400m, but more specifically above the thermocline. Other studies such as Saraswat and Khare (2010) and Niebler et al (1999) are in agreement with Hemleben et al (1989) with estimates of 0-200m and 0-100m, respectively. This species is constrained by sea surface temperatures of 0 to 27 C with peak abundance occurring between 3 and 19 C (Bé and Tolderlund, 1971).…”
Section: Introductionsupporting
confidence: 78%